Serangan Arthroschista hilaralis Walk. (Lepidoptera: Pyralidae) pada tegakan jabon (Neolamarckia cadamba [Roxb.] Bosser) di Sumatera Selatan - Sri Utami; Hermanu Triwidodo; Pudjianto Pudjianto; Aunu Rauf; Noor Farikhah Haneda (Perhimpunan Entomologi Indonesia, 2018)
Infestation of pest is a major problem in the seedling and field of Jabon (Neolamarckia cadamba [Roxb.] Bosser) in Indonesia, especially in South Sumatra. Arthroschista hilaralis Walk. (Lepidoptera: Pyralidae) is one defoliator pest attacked jabon stands. Some information about the infestation of A. hilaralis are required for pest control and prevent. The objective was to study the incidence level and intensity level of A. hilaralis on jabon stands at the planting age 2 and 4 years at the 2 seasons, and analyze the effect of weather (temperature and humidity) to foliar damage caused by A. hilaralis. This experiment was conducted in six locations in South Sumatra. The plots were delineated in three area that each plot was 0.03 ha in area and contain 20 jabon trees. Observations on the incidence and intensity level of A. hilaralis were conducted every month for 16 months representing two categories of time point observation of the rainy season and dry season. The results showed that infestation of A. hilaralis on jabon stands at the planting age 2 years and the rainy season was higher than planting age 4 years and another season. The incidence level and intensity level of A. hilaralis were 74.45% and 55.21% respectively. Weather factors (e.g. temperature and humidity) thought affected the incidence level and intensity level of A. hilaralis. Temperature has negative correlation to the incidence level of A. hilaralis (r = -0.629; p = 0.009) and to the intensity level of A. hilaralis (r = -0.546; p = 0.029). Humidity has positive correlation to the incidence level of A. hilaralis (r = 0.900; p < 0.0001) and to the intensity level of A. hilaralis (r = 0.768; p = 0.0005).